2021
DOI: 10.1186/s13019-021-01558-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of body mass index on early and mid-term outcomes after surgery for acute Stanford type A aortic dissection

Abstract: Background Obesity is dramatically increasing worldwide, and more obese patients may develop aortic dissection and present for surgical repair. The study aims to analyse the impact of body mass index (BMI) on surgical outcomes in patients with acute Stanford type A aortic dissection (ATAAD). Methods From January 2017 to June 2019, the clinical data of 268 ATAAD patients in a single centre were retrospectively reviewed. They were divided into three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Moreover, 2 independent retrospective cohort studies in Japan [ 7 , 8 ] and 1 in Italy [ 22 ] identified obesity (BMI ≥ 30.0) as a risk factor of in-hospital mortality in ATAAD patients who underwent surgical repairs (OR = 3.00, 95% CI: 1.40–6.20, OR = 3.16, 95% CI: 1.48–6.74, and OR = 2.14, 95% CI: 1.22–3.78). However, a retrospective cohort study conducted in Germany [ 9 ] and 2 in China [ 10 , 24 ] found no associations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, 2 independent retrospective cohort studies in Japan [ 7 , 8 ] and 1 in Italy [ 22 ] identified obesity (BMI ≥ 30.0) as a risk factor of in-hospital mortality in ATAAD patients who underwent surgical repairs (OR = 3.00, 95% CI: 1.40–6.20, OR = 3.16, 95% CI: 1.48–6.74, and OR = 2.14, 95% CI: 1.22–3.78). However, a retrospective cohort study conducted in Germany [ 9 ] and 2 in China [ 10 , 24 ] found no associations.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies reported that obesity raised the risk of perioperative mortality of ATAAD [ 7 , 8 ]. However, other studies failed to demonstrate a significant association between body mass index (BMI) and perioperative mortality of ATAAD [ 9 , 10 ]. Relatively low sample size and single-center design of most previous studies may contribute to controversial conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, employing wound care protocols designed for patients with diminished tissue repair mechanisms, as well as personalized postoperative nutritional plans to promote recovery. This underlines the efficacy of the surgical approach and postoperative management, suggesting that while obesity presents certain complexities, they can be adeptly managed with the right surgical strategy and postoperative care (21,22).…”
Section: Discussionmentioning
confidence: 98%
“…But the mortality was similar to previous reports in our center. [ 36 ] The mortality between 2 groups has no significant difference.…”
Section: Discussionmentioning
confidence: 99%